Synthesis, Structure, and Electrochemical Properties of a Sulfur-Carbon Replica Composite Electrode for All-Solid-State Li-Sulfur Batteries. Issue 1 (5th December 2016) - Suzuki, Kota; Tateishi, Mitsuru; Nagao, Miki; Imade, Yuki; Yokoi, Toshiyuki; Hirayama, Masaaki; Tatsumi, Takashi; Kanno, R.
Abstract : Carbon replica constructed of three-dimensional, ordered mesopores was employed as the conductive framework for the composite electrode in Li-sulfur all-solid-state batteries. Using a gas-phase mixing method under various conditions, elemental sulfur was introduced into the mesopores with an average diameter of 12 nm. The all-solid-state cells consisted of the sulfur-carbon replica composite cathode, thio-LISICON solid electrolyte, and Li-Al alloy anode. The cells produced discharge capacities of approximately 1500 mAh g −1 in the 1 st cycle, which is comparable to the theoretical capacity of sulfur. Thermogravimetric and X-ray diffraction analyses revealed that sulfur deposited inside the mesopores is the main contributor to the excellent performance of the battery. However, sulfur strongly interacted with the carbon replica, reducing the thickness of the carbon wall from 7 to 4 nm. This structural change in the carbon matrix triggered the deterioration of battery performance, especially the cycling capability. Optimizing the sulfur deposition conditions could therefore enhance the performance of batteries using such composite electrodes.